The Legal Protection of Creditors Who Do Not Respond to Payment Offers in Bankruptcy Settlement - Primaditha, Anindya Putri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to find out and explain legal protection for creditors who have never responded to offers of cash payments in bankruptcy settlements, and settlement of accounts payable against these creditors based on case studies of Central Jakarta District Court Decision Number 364/Pdt.P/2020/PN. Jkt. Pst. The approach method uses normative juridical methods. The research specifications are analytical descriptive. The type of data is secondary legal data, consisting of primary legal materials, namely the 1945 Constitution, statutory regulations and court decisions; secondary legal materials such as books and journals, as well as tertiary legal materials. Data collection method is done by literature study or document study. Methods of data analysis using qualitative data analysis method. The results of the study show that legal protection for creditors who do not respond to offers of cash payments must be pursued through curators, namely submitting offers of cash payments on deposit/consignment, and requesting approval from the court if the creditors still do not respond; court institutions, through judges, clerks and bailiffs according to their duties and authorities; and the existence of written regulations as a basis in efforts to protect the law against these creditors. If the creditor does not respond, then Article 1404 jo. 1381 of the Civil Code, and the cash payment offer was ratified by the District Court.Keywords: Bankruptcy; Consignment; Payment Offer; Protection.